2008
DOI: 10.1097/brs.0b013e31816b4619
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of Bone Marrow Mesenchymal Stem Cells and Nucleus Pulposus Cells Modulate Gene Expression Profile Without Cell Fusion

Abstract: This study clarifies the mechanism of MSCs and NPCs interaction in a 3-dimensional environment, excluding cell fusion. These data support the use of undifferentiated MSC for stem cell therapy for IDD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 33 publications
6
112
0
2
Order By: Relevance
“…In our own preliminary study, human NP cell culture conditions were consistent with those described by both Le Maitre et al (1) and Sakai et al (5), but differed with regard to the process of digestion with collagenase overnight, as described in other studies (10,11). Furthermore, we found that cell clusters, as one of the hallmarks of degeneration, diminished gradually in a monolayer culture within 48 hours of initial culture ( Figure 1).…”
Section: To the Editorsupporting
confidence: 75%
See 1 more Smart Citation
“…In our own preliminary study, human NP cell culture conditions were consistent with those described by both Le Maitre et al (1) and Sakai et al (5), but differed with regard to the process of digestion with collagenase overnight, as described in other studies (10,11). Furthermore, we found that cell clusters, as one of the hallmarks of degeneration, diminished gradually in a monolayer culture within 48 hours of initial culture ( Figure 1).…”
Section: To the Editorsupporting
confidence: 75%
“…For example, the capsule around NP cells in vivo, which is a distinct pericellular matrix or "nest" (8), is lost in cultures using alginate (9). Nevertheless, among studies, there are variations in the conditions of monolayer cultures of human NP cells (1,5,10,11), including variations in diverse digestion medium and duration. These scenarios reflect the earliest stages of investigations into NP cells in human intervertebral discs.…”
Section: To the Editormentioning
confidence: 99%
“…An attractive alternative for AF tissue engineering would be the use of hMSCs. However, while hMSCs can differentiate in NP cells [8,10,26], differentiation into AFCs has not been demonstrated yet. Sobajima et al [27] showed that, 24 weeks after MSCs transplantation in normal rabbit disc, MSCs were localized in the inner AF, where they exhibited an apparent change in morphology to a spindle shape more similar to native AFCs.…”
Section: Discussionmentioning
confidence: 99%
“…Exciting advances in the field of tissue engineering have allowed spine researchers to begin developing novel therapeutic approaches in an attempt to intervene in and modulate the course of IVD degeneration by repairing, replacing or regenerating the herniated or degenerated NP [7][8][9][10]. However, these strategies are ineffective without a functional annulus fibrosus (AF) able to withstand the physiological intradiscal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Steck et al has suggested that MSCs can adopt a gene expression profile resembling native disc cells but the molecules they examined for are also found in cartilage tissue [111]. Co-culturing MSC with disc cells appears to speed up the conversion to a chondrogenic/discogenic phenotype [57,90,118], possibly via paracrine effects or cell-cell interactions. The effect of implantation of MSCs or adipose derived stem cells have been studied in vivo in animal models and appear promising but have not as yet been used to repair human discs [97,108,125].…”
Section: Stem Cellsmentioning
confidence: 99%